2013
DOI: 10.1021/am402618w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Size and Shape on Biofilm Eradication for Nitric Oxide-Releasing Silica Nanoparticles

Abstract: Nitric oxide (NO), a reactive free radical, has proven effective in eradicating bacterial biofilms with reduced risk of fostering antibacterial resistance. Herein, we evaluated the efficacy of NO-releasing silica nanoparticles against Gram-negative Pseudomonas aeruginosa and Gram-positive Staphylococcus aureus biofilms as a function of particle size and shape. Three sizes of NO-releasing silica nanoparticles (i.e., 14, 50, and 150 nm) with identical total NO release (∼0.3 μmol/mg) were utilized to study antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 44 publications
5
143
1
Order By: Relevance
“…6 Moreover, Slomberg et al found that the decreased size and increased aspect ratio could enhance the anti-biofilm efficiency of the NO-releasing silica nanoparticles. 5 However, in our study, W-CHX with wire shape did not show a better anti-biofilm efficiency than S-CHX, partly due to the entanglement of W-CHX that may restrict the release of CHX. The nanoparticle encapsulation per se still improves the anti-biofilm efficiency of CHX.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…6 Moreover, Slomberg et al found that the decreased size and increased aspect ratio could enhance the anti-biofilm efficiency of the NO-releasing silica nanoparticles. 5 However, in our study, W-CHX with wire shape did not show a better anti-biofilm efficiency than S-CHX, partly due to the entanglement of W-CHX that may restrict the release of CHX. The nanoparticle encapsulation per se still improves the anti-biofilm efficiency of CHX.…”
Section: Discussioncontrasting
confidence: 72%
“…1 Previous in vitro and in vivo studies have reported the promising capacity of MSNs as anticancer and antibacterial drug delivery systems. [2][3][4][5][6] Moreover, our group has recently successfully encapsulated the most commonly used antimicrobial agent in dentistry, chlorhexidine (CHX), into commercial MSNs (MCM-41), and further confirmed their antibacterial and anti-biofilm efficiencies via an effective releasing mode. 7 There are plenty of studies on how the nanoparticle morphology, size, and surface modifications affect their interactions with the mammal cells.…”
Section: Introductionmentioning
confidence: 90%
“…In addition, bacterial biofilms are "a breeding ground" for frequent resistance mutations and the exchange and alteration of these mutations among different bacterial cells. 15 Studies have shown that many NPs can prevent or overcome biofilm formation, including Au-based NPs, 37 Ag-based NPs, 38 Mg-based NPs, 39 NO NPs, 40,41 ZnO NPs, 7 CuO NPs, Combatting microbes using multiple mechanisms simultaneously…”
Section: Overcoming the Existing Antibiotic Resistance Mechanismsmentioning
confidence: 99%
“…15 To date, several NO-releasing NPs such as silica, gold, liposomes, and dendrimers have been developed by taking advantage of nanotechnology and NO. [16][17][18][19][20][21][22] However, these NO-releasing NPs showed an initial burst release probably due to the NO tethering only to the surface of the NPs. This was accompanied by a relatively short duration of NO release ranging from a few to up to 24 hours.…”
Section: Introductionmentioning
confidence: 99%